The Wizard of Oz - "Baum, L.Frank" (MM publications: London, 2001)
A classic story adapted to suit the needs of young learners about the adventures of Dorothy and her dog Toto after a tornado whisks them away from their home in Kansas to the fantastic, magical land of Oz
Keywords: Friendship-English Fiction